Use of Passiflora incarnata L. in the alternative treatment of generalized anxiety disorder (Research, Society and Development, 2020)
This study is a bibliographic, qualitative and descriptive research on the importance using of Passiflora incarnata as a phytopharmaceutical used in the search for a viable and more accessible alternative, seeking to contribute in the alternative treatment of generalized anxiety disorder. In this sense, it is good to clarify the terminology "anxiety", which is then described as an emotional state present in different moments of life, as well, in the rush of everyday life. The symptoms are manifested through pessimistic thoughts, afflictions, anguish and in moments from disturbances, such as what we are going through with the COVID-19 pandemic and its dangers of infection, illness and lack of concise information. Countless synthetic drugs such as benzodiazepines are used to treat symptoms and control the traumatic manifestations that anxiety carries. However, the continuous use of synthetic anxiolytic drugs, among others, causes emotional exhaustion, daily stress and dependence, always causing higher doses. Another serious problem is the association of these with other pharmaceutical drugs, well, the ingestion of alcoholic beverages, causing irritability, mental uncontrolling, coma and death. A possible alternative and safe suggestion is the use of phytopharmaceuticals such as Passiflora incarnata, which in numerous studies have shown as an efficient option for the treatment of anxiety, due to the good results in the symptomatological control and in the joint association between other plant and synthetic drugs.